Praktik Keagamaan Jama’ah Tabligh di Markas Madani Medan Marelan : Studi Kehidupan Jama’ah Tabligh, Kec. Labuhan Deli, Kab Deli Serdang, Sumatera Utara - Pranoto, Doni (CV. Ulil Albab Corp, 2024)
This study aims to describe religious practices and the influence of religious practices on social interaction between followers and the surrounding community who do not join. This type of research uses qualitative research with a descriptive approach. The subjects in this study were the amir (leader), the congregation who joined and the surrounding community who did not join. Data collection techniques in this study were observation, interviews and documentation. The findings of this study show an overview of religious practices and those that result in social interaction with congregations and the surrounding community at Medan Marelan Madani Headquarters, and this research is going very well. Their religious practices in Madani maraks focus on several objects, namely khuruj, jaulah traditions, eating together, ta'lim wa ta'lum, social interaction and the views of the local community. In carrying out their religious practices, they carry out sincere intentions for Allah, namely da'wah efforts. The interaction of the Tabligh congregation with the surrounding community is well established, in which their relationship is proven by their acceptance there and until now there has never been a clash between the Tablighi Jama'ah and the surrounding community.